Civic Identity of Ukrainians: Age, Gender, Political Dimensions - Petrovska Inha (Insight: the psychological dimensions of society, 2024)
This article aims to determine and analyze the peculiarities of the civic identity of Ukrainian citizens of different ages, genders, and political orientations. Methods: survey, testing (“Diagnostics of Maturity and Type of Civic Identity” (Petrovska, 2021), “Political Orientation” (Karkovska, 2011)), descriptive statistics, frequency analysis, comparative analysis (t-test, ANOVA, Scheffé test). Results. Statistically significant differences in persons of different age groups were revealed by such characteristics as representation, conceptuality, subjectness orientation, and integral indicator of civic identity maturity. Citizens of middle adulthood have higher values of representation and conceptuality of civic identity; citizens of early adulthood have higher values of the subjectness orientation of civic identity; citizens of young age have lower values of the integral indicator of civic identity maturity. Statistically significant differences between men and women were determined for such characteristics as representation, subjectness orientation, conceptuality, and integral indicator of civic identity maturity. They are higher in men than in women. Statistically significant differences were found between citizens with right-wing and left-wing political orientations by such characteristics as subjectness orientation and stability. Citizens who share right-wing political views have higher values of subjectness orientation but lower values of stability of civic identity. Statistically significant differences were detected between supporters of democracy and authoritarianism by such characteristics as conceptuality, representation, and the maturity of civic identity. Among citizens who support democracy (recognition and implementation of democracy) and share democratic values, these indicators are higher than among supporters of authoritarianism. Conclusion. It was empirically proven that there are differences in indicators of the maturity of civic identity in women and men, representatives of different age groups, and political orientations. The prospect of further research is the development of programs to stimulate the formation of a mature civic identity, considering the clarified age, gender, and political features of the civic identity of Ukrainians.